Una propuesta de tipo investigativo - interventivo para construir resiliencia (2012)
The following article is a continuation of the reflections treated in the master thesis "Procesos de construcción narrativa que organizan experiencias resilientes en familias en situación de desplazamiento, en la interacción institución familia" (articulated with the Master of Clinical Psychology and Family of Universidad Santo Tomás ), where the investigative purpose was understood as the processes of narrative construction, and the intervention purpose was to mobilize these processes towards the emergence of resilient experiences; The text shows some results of interventional intention, exposing concepts that define resilience from different perspectives, it then presents connections between these meanings of resilience and processes of narrative construction. Finally, ideas are proposed about how in reflexive conversation scenarios, processes can be mobilized towards building resilient experiences.